Reforming security industry training standards: an Australian case study - Prenzler, Tim (International journal of comparative and applied criminal justice, 2017)
This article critiques recent developments in training in the Australian security industry. Regulation of the industry is state- and territory-based, with eight jurisdictions enacting purpose-built legislation. Training was a key area of reform in the 1990s and early 2000s, but standards remained fragmented until 2008 when the Committee of Australian Governments agreed on a national competency framework to be implemented by 2010. However, despite the adoption of a common curriculum for core security tasks, the project derailed spectacularly in terms of consistency of standards, as revealed by a number of major inquiries and associated sources. This article analyses the reasons for this situation and recommends an alternative model to optimise competency standards in security work that includes much greater specificity in hours of instruction and in teaching and assessment methods. The lessons from this study have wider application given that deficits in security training appear to be a common problem internationally.